Noise And Vibration Study Of Commercial Conveyor System - Rajasagaran, Kogulan (Universiti Sains Malaysia, 2018)
Chain conveyors are one of the machines used in various type of industries as they provide a convenient mean of transport for goods within the industry. The chain conveyor used in this study is FlexMove FL 150 series chain conveyor which is provided FlexMove System Sdn. Bhd. This particular chain conveyor encounters vibration and noise problem. When the conveyor is under operation, the vibration and noise issue found in the conveyor system contributes to an unhealthy working environment for operators. The aim of this project is to attenuate the vibration and noise level of the whole structure at the operating frequency range. In this project, tuned damped dynamic vibration absorber (DVA) was deployed on the conveyor structure to attenuate the vibration and noise level. The damped DVA was designed as a cantilever beam and together with viscoelastic material as damper. Microflown Scan & Paint sound measurement was conducted to determine sound pressure levels from the structure. For vibration signal acquisition from the structure, LK-G Laser Head displacement experiment, Modal Analysis and Spectral Analysis were conducted. Modal analysis was the platform to execute structural dynamic modification through simulation. The tuned damped DVA was attached to the conveyor structure and the attenuation of vibration and noise level is assessed by repeating the measurements. Modal analysis of the improved conveyor proves that the vibration amplitude is reduced by 9.59% with the attachment of tuned damped DVA. The acoustic measurements show that the improved conveyor endures maximum sound pressure level reduction of 2.5dB(A).